The association between adolescent height and feelings is sex-specific - Eric Fiedler; Christiane Scheffler (Human Biology and Public Health, 2026)
Background Previous studies have shown associations between human growth and socioeconomic conditions. As these conditions are often associated with feelings of well-being and mental health, these feelings may in turn be associated with body height. The present study was conducted to determine the contribution of specific feelings to the growth of young adolescents. Methods The study surveyed a total of 240 early pubertal boys (aged 12–13 years) and 98 early pubertal girls (aged 11 years). The study included height and data on mental and emotional well-being across various areas of life obtained from questionnaires of the KiGGS Wave 2, a comprehensive study conducted by the Robert Koch Institute (RKI) on the health of children and adolescents living in Germany. Results Early pubertal boys and girls differ in their patterns of associations between feelings and body height. In contrast to expectation, taller height in girls is associated with negative feelings, shorter height is associated with the feeling “energy”. Shorter height in boys was mildly associated with a higher level of “worries”. Conclusion The present study provides new insights into the relationships between feelings and height during early pubertal age. The findings suggest that gender-specific roles influence physical growth. It is speculated that tradwife effects and aspects of mate selection exhibit effects on height in young adolescents.